THE INFLUENCE OF MARKETING MIX AND SERVICE QUALITY ON CORPORATE REPUTATION AND ITS IMPACT ON REPURCHASE DECISION - Aam Bastaman; Mufti Royyansyah (MIX: JURNAL ILMIAH MANAJEMEN, 2017)
Abstract. Retail business is a growing Industry in Indonesia. Among others there aretwo important variables in retail business: Marketing mix and service quality. Thisresearch are aimed first to know and to analysis the influence of marketing mix andservice quality on corporate reputation and its impact on repurchase decision directlyand indirectly. Secondly, to analysis which variables affect mostly on corporatereputation and on repurchase decision. The research approaches using quantitativeapproach with survey method. Tool for the statistical test used structural equationmodeling (SEM) with LISREL 8.7 software. There are 200 respondents involved,mostly are middle income people. Method of sampling used non probability samplingmethod in particular by accidental sampling. The results: Marketing mix directlyinfluenced corporate reputation and repurchase decision directly and indirectly mediatedby corporate reputation. In the other hand, service quality directly did not influencecorporate reputation it also did not influence decision to repurchase directly andindirectly through corporate reputation. Lastly, corporate reputation directly influencedrepurchases decision. Implication of the research it is obvious in retail industrycustomer decision on repurchase is highly based on and influenced by marketing mix,especially pricing policy and decision.